Analysis of half-sib progenies of sapota (Manilkara zapota ) for dwarf stature and fruit quality - P C Tripathi; A Rekha; Anuradha Sane; M R Dinesh (Current Horticulture, 2025)
The evaluation of 116 half-sib progenies of sapota (Manilkara zapota Royen) var. Cricket Ball was carried out for 6 years (2017- 2022), at ICAR-IIHR,Bengaluru to develop a promising variety characterized by dwarf growth habit, high productivity, and quality fruits. All the progenies were evaluated for growth, yield, fruit, and biochemical parameters. Correlation among different yieldcontributing traits in half-sib progenies revealed that yield was strongly correlated with the number of fruits (r=0.945) while the tree height showed a positive and significant correlation with tree volume (r=0.904) and tree spread (r=0.854). Regression analysis indicated a strong positive relationship between yield and both fruit weight and the number of fruits/tree. Half-sib progenies were grouped into seven clusters based on Euclidean distance, with the S-63 forming a separate single cluster with all desirable traits. Among half-sibs, one half-sib line, S-63, with desirable traits has been identified, multiplied and further evaluated in a row trial with Cricket Ball as the control for three years (2020-2022). In row trial, the progeny S-63 recorded a low tree height (1.95 m) and a high yield (90.21 fruits/tree), compared to Cricket Ball which recorded a tree height of 2.15 m and a yield of 10 fruits per tree at the sixth year. The average yield of S-63 was higher at 48.37 fruits per tree (5.9 kg) compared to Cricket Ball (13.67 fruits/tree; 1.4 kg). Fruit weight of S-63 (128.57 g) was higher compared to Cricket Ball (114 g). The TSS (20.33°Brix), and acidity (0.29%) were higher compared to Cricket Ball (19.66°Brix; 0.2%). Thus, S-63 was found to be the best performing line for yield, dwarf stature fruit and quality fruits